Variability of the Nearshore Wave Climate in the Eastern Part of the Black Sea - Saprykina, Yana; Shtremel, Margarita; Aydoğan, Burak; Ayat, Berna (Springer Basel Ag, 2019)
The variability in nearshore wave climate of the eastern part of the Black Sea was studied based on 38 years of wave hindcast data from spectral wave modelling for the period from 1979 to 2016. Correlation analysis has revealed the spatial inhomogeneity within the region on the short timescale from a few hours to one day, with the southern part being more homogeneous than the northern one. The variability of annual mean wave heights in these two regions were compared using wavelet correlation analysis. The wave climate variability at four chosen locations subject to wave modelling was correlated with climate indices (NAO, AO, AMO, PDO and EA/WR) on the following timescales: 20-30, 10-17 and 4-7 years. Despite the fact that the selected periods of fluctuations of average annual wave heights are almost the same for the chosen locations due to changes in climatic indices, a decrease or increase in amplitudes of the same frequency (multi-annual and decennial) can occur in antiphase even within the same coast. Such behavior is probably caused by complex inhomogeneous wind conditions near the coast. Fluctuations of annual mean wave heights of southern and northern coasts correlate with teleconnection patterns in antiphase on multi-decadal periods of about 20-30 years. To conclude, the nearshore wave climate variability of the eastern part of the Black Sea is inhomogeneous and therefore it can be divided at least into three regions: northeastern, northwestern and southern.
Keywords: Wave climate; coastal zone; teleconnection patterns; numerical modelling